THE INFLUENCE OF INTERNAL COMMUNICATION AGAINST THE EFFECTIVENESS OF THE SERVICE IN THE OFFICE OF THE HEAD OF MANDOLANG REGENCY OF MINAHASA IN NORTH SULAWESI PROVINCE - Tarigan, Jenni Yolanda Br.; Rumapea, Patar; Kolondam, Helly (Sam Ratulangi University, 2017)
The purpose of this research is to know the extent of the influence of communication internalagainst the effectiveness of the sevices in the Office of the head of Mandolang District Minahasa in NorthSulawesi Province. This research using quantitative research methods. With the samples used is SaturatedSampling are 35 people. Based on a simple linier regression analysis showed that there is influence ofinternal communication between (X) and (Y) work efficiency. It is evident simple linier regression equationof Y=14,613 + 0,538 X + e. for calculation of the correlation relationship is category of being, This evidencedby the r value 0,565 interpretation advanced by Sugiono are in the interval (0,00-0,199). And the value ofthe coefficient of determination is 31,9% indicating that the influence of internal commucation against theeffectiveness of the service namely 31,9% and the rest is 68,1% influenced by variables that are not includedin this research.From the results of the comparism of the value of a sig (0,03) a (0,05) these authors conclude thatinternal influential communication significantly to the effectiveness of the sevices Head Office Mandolangin the Regency of Minahasa in North Sulawesi province. Then the hypothesis in this study was acceptedH1and H0 denied.Keywords: Internal Communication, The Services Effectiveness